Gastric lymphoma - epidemiology, clinical manifestations and current therapy management - Adrian Hunek; Magdalena Alicja Zapała; Karolina Chmielarz; Karolina Kaziród; Joanna Wiśniewska-Skomra; Kinga Tylutka; Anna Hapon; Mikołaj Dadziak (Kazimierz Wielki University, 2023)
Gastric lymphoma is a rare malignant disease, which in recent years has been showing an increasing incidence in the population. The development of MALT is most often the result of chronic Helicobacter pylori infection. Further chronic inflammation may result in malignant transformation of MALT to high-grade diffuse large B-cell lymphoma (DLBCL). However, DLBCL lymphomas most often arise de novo. The risk of primary gastric lymphoma increases with age. The symptoms of gastric lymphoma are very diverse and non-specific, which is why the knowledge about this disease and the differential diagnosis of diseases with similar symptoms play a very important role. The gold standard for diagnosing gastric lymphomas is upper GI endoscopy with biopsy, and sometimes additional imaging tests are necessary to make a proper diagnosis. It is very important to start treatment quickly - the first-line treatment is the eradication of Helicobacter pylori bacteria. Currently, we also have other therapeutic pathways that can change the course of the disease. The therapeutic plan should be individually selected for the needs of the individual patient. Changes detected in the early stages and treated quickly give patients a good chance of being cured. This publication is an attempt to summarize the current state of knowledge about the epidemiology, etiopathogenesis, clinical picture and therapeutic strategies in the case of gastric lymphoma.